Integrated near-field thermo-photovoltaics for heat recycling - Gaurang R. Bhatt (Nature Portfolio, 2020)
Designing a scalable platform to generate electricity from the energy exchange mechanism between two surfaces separated by nanometer distances remains a challenge. Here, the authors demonstrate reconfigurable, scalable and fully integrated near-field thermo-photovoltaics for on-demand heat recycling.